Stability of all-inorganic perovskite solar cells. (January 2020) - Ouedraogo, Nabonswende Aida Nadege; Chen, Yichuan; Xiao, Yue Yue; Meng, Qi; Han, Chang Bao; Yan, Hui; Zhang, Yongzhe
Abstract: Organometal lead halides perovskites are promising solar cells material due to their outstanding properties such as tuneable bandgap, impressive tolerance to defects, long exciton diffusion length, high carrier mobility and absorption coefficient. Up to now, the organometal lead halides based solar cells (PSCs) have demonstrated impressive power conversion efficiency reaching 25.2% (not stabilised). However, their operating life-times are limited due to degradation of the organic components under some environmental conditions. Therefore, researchers have focused their interest on the all inorganic perovskite; especially on the caesium lead triiodide perovskite (CsPbI3 ) which exhibits a better compositional and chemical stability. Nevertheless, the phase instability of the black phase of this material constitutes its main limitation for its use in the solar cell devices production. This review aims to present the most impactful research giving insights on the factors that may cause the instability of all-inorganic lead halide perovskite materials, as well as the instability of the whole device. In addition to deposition methods, the composition, structure and optical properties of inorganic perovskite materials have also been presented. Furthermore, this review highlights the different strategies used in order to improve the phase stability of caesium lead halide perovskite material through either engineering on the material structure or the fabrication method. Graphical abstract: Image 1 Highlights: The most relevant studies on the stability of all-inorganic PSCs materials and preparation methods are reviewed. The effects of different engineering/modifications methods on the phase stability of CsPbI3 are reviewed. The influence of the different layers on the device efficiency and stability are pointed out.